Granice wolności - Gajda, Janusz (Horyzonty Wychowania, 2017)
The keynote of the article is the statement that freedom as one the most appreciated values nowadays, of indisputable importance in every man’s life and in the lives of societies may assume completely different axiological tinge. Therefore, it demands that man be aware of moral principles of choices made and delineate on this basis the limits of his conduct. Detailed discussion refers to the analysis of the essence of freedom, its place in the hierarchy of values and connection with human dignity. Then, the author deals with external freedom and internal freedom as the basis for dignity-like human behaviours and his moral responsibility. Finally, he discusses freedom in a trap of liberalism and fundamentalism. The author leaves an open question about the limits of freedom in the context of contemporary socio-cultural events and situations, at the same time indicating the necessity of education towards freedom